Indigenous peoples - Bodkin-Andrews, Gawaian; Mooney, Janet; Craven, Rhonda G. (International advances in education., 2013)
International Advances in Education: Global Initiatives for Equity and Social Justice is an international research monograph of scholarly works that are seeking to advance knowledge and understanding of a diverse range of Indigenous or First Peoples across the globe. With the overarching emphasis being towards education, this collection of works outlines the unique history, policy, and lived experiences of Indigenous peoples within education systems around the world. The volume itself is split into three sections that offer: (i) an overview of the past and current educational conditions of Indigenous peoples; (ii) policy and practice aimed at enhancing cultural inclusiveness and resisting deculturalization, and (iii) finally the identification of pedagogical factors that may be important for the educational progress of a diversity of Indigenous students. Overall, this volume will act as a valuable source for those seeking to maintain and restore Indigenous cultures and languages within the education system, as well as identifying other methods and practices that may increase the engagement and resilience of Indigenous students within a variety of education settings. As a result, this collection of works will be a valuable tool for educators, researchers, policy makers, and school counselors who may be seeking to further understand the experiences of Indigenous students within the education system.